Single-cell RNA-seq reveals cellular heterogeneity of mouse carotid artery under disturbed flow - Li, Fengchan (Cell Death Discov, 2021)
Disturbed blood flow (d-flow) has been known to induce changes of the cells in the arterial wall, increasing the risk of atherosclerosis. However, the heterogeneity of the vascular cell populations under d-flow remains less understood. To generate d-flow in vivo, partial carotid artery ligation (PCL) was performed. Seven days after ligation, single-cell RNA sequencing of nine left carotid arteries (LCA) from the PCL group (10,262 cells) or control group (14,580 cells) was applied and a single-cell atlas of gene expression was constructed. The integrated analysis identified 15 distinct carotid cell clusters, including 10 d-flow-relevant subpopulations. Among endothelial cells, at least four subpopulations were identified, including Klk8(hi) ECs, Lrp1(hi) ECs, Dkk2(hi) ECs, and Cd36(hi) ECs. Analysis of GSVA and single-cell trajectories indicated that the previously undescribed Dkk2(hi) ECs subpopulation was mechanosensitive and potentially transformed from Klk8(hi) ECs under d-flow. D-flow-induced Spp1(hi) VSMCs subpopulation that appeared to be endowed with osteoblast differentiation, suggesting a role in arterial stiffness. Among the infiltrating cell subpopulations, Trem2(hi) Mφ, Birc5(hi) Mφ, DCs, CD4(+) T cells, CXCR6(+) T cells, NK cells, and granulocytes were identified under d-flow. Of note, the novel Birc5(hi) Mφ was identified as a potential contributor to the accumulation of macrophages in atherosclerosis. Finally, Dkk2(hi) ECs, and Cd36(hi) ECs were also found in the proatherosclerotic area of the aorta where the d-flow occurs. In conclusion, we presented a comprehensive single-cell atlas of all cells in the carotid artery under d-flow, identified previously unrecognized cell subpopulations and their gene expression signatures, and suggested their specialized functions.